2011
DOI: 10.1111/j.1095-8339.2011.01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Growing coffee: Psilanthus (Rubiaceae) subsumed on the basis of molecular and morphological data; implications for the size, morphology, distribution and evolutionary history of Coffea

Abstract: Morphological and molecular phylogenetic studies show that there is a close relationship between Coffea and Psilanthus. In this study we reassess species relationships based on improved species sampling for Psilanthus, including P. melanocarpus, a species that shares morpho-taxonomic characters of both genera. Analyses are performed using parsimony and Bayesian inference, on sequence data from four plastid regions [trnL-F intron, trnL-F IGS, rpl16 intron and accD-psa1 intergenic spacer (IGS)] and the internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
140
0
23

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(171 citation statements)
references
References 48 publications
8
140
0
23
Order By: Relevance
“…Since all the coffee cherries from all production systems were subjected to the same processing method (wet processing method which contribute to best color and shape and make of coffee bean), the observed variation could be due to the botanical variability or growth environment. Davis et al (2011) also confirmed that the green bean color was best where the mucilage had removed by fermentation under water in wet processing and the poorest color was obtained when the bean dried inside the fruit.…”
Section: Discussionsupporting
confidence: 57%
“…Since all the coffee cherries from all production systems were subjected to the same processing method (wet processing method which contribute to best color and shape and make of coffee bean), the observed variation could be due to the botanical variability or growth environment. Davis et al (2011) also confirmed that the green bean color was best where the mucilage had removed by fermentation under water in wet processing and the poorest color was obtained when the bean dried inside the fruit.…”
Section: Discussionsupporting
confidence: 57%
“…O gênero Coffea é representado por mais de 120 espécies, destacando-se comercialmente as espécies: Coffea arabica e C. canephora (DAVIS et al, 2011). A produção média mundial do café nos últimos anos foi superior a 140 milhões de sacas, produzido principalmente, nos países considerados em desenvolvimento (ICO, 2013).…”
Section: Introductionunclassified
“…The genus Coffea comprises at least 124 species, of which Coffea arabica and C. canephora are economically important (Davis, Tosh, Ruch, & Fay, 2011). Despite C. arabica being the most widely farmed species in the world, the cultivation of C. canephora (Conilon coffee) has significantly contributed to coffee production worldwide.…”
Section: Introductionmentioning
confidence: 99%